Tradycje i obyczaje szkolne w „pamięci” nauczycieli oraz uczniów na terenie zaboru austriackiego - Grabowska, Dorota (Biuletyn Historii Wychowania, 2014)
The purpose of this article is to explore the traditions and customs commemorated by the school community from the Austrian annexation. It presents their involvement in the celebration of national anniversaries (e. g. the adoption of the Constitution of May 3, the battle of Raclawice, uprisings) and religious ones (including Christmas, Easter, Corpus Christi, All Souls’ Day). On the other side, it shows events associated with Polish education (e. g. National Commission of Education day) and also the functioning of the school (school anniversaries, the day of the patron saint of the school). It takes into consideration the ways of commemorating the achievements of people who contributed to the history of Polish learning and culture (e. g. Tadeusz Kościuszko, Adam Mickiewicz, Juliusz Słowacki). In addition, it explores the attitudes of the teachers to Polish traditions and customs. The above issues are illustrated on the basis of selected diaries and memoirs written by pupils and teachers.